1985
DOI: 10.1136/adc.60.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Congenital microvillous atrophy: specific diagnostic features.

Abstract: SUMMARY Proximal small intestinal and colonoscopic mucosal biopsies from two children with the intractable diarrhoea of infancy syndrome were examined by electron microscopy. Microvillous involutions were found in the small and large bowel of both patients. We suggest that this is a specific diagnostic finding for congenital microvillous atrophy, a distinct disorder within the intractable diarrhoea syndrome which has an extremely poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
15

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 9 publications
4
80
0
15
Order By: Relevance
“…Microvillus inclusion disease is a congenital enteropathy of intractable diarrhea. Both the molecular defect and the pathophysiology of this disease are unclear, but its main feature includes villus atrophy, loss of microvilli, and the presence of intracytoplasmic inclusions, vacuoles containing brush-border-like microvilli called microvilli inclusions (29). More recently, it has been shown that decreased expression of apical membrane transporters such as NHE-2, NHE-3, and sodium glucose transporter is observed in microvillus inclusion disease samples (30).…”
Section: Discussionmentioning
confidence: 99%
“…Microvillus inclusion disease is a congenital enteropathy of intractable diarrhea. Both the molecular defect and the pathophysiology of this disease are unclear, but its main feature includes villus atrophy, loss of microvilli, and the presence of intracytoplasmic inclusions, vacuoles containing brush-border-like microvilli called microvilli inclusions (29). More recently, it has been shown that decreased expression of apical membrane transporters such as NHE-2, NHE-3, and sodium glucose transporter is observed in microvillus inclusion disease samples (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we referred to group I as 'immune enteropathy group' because it has been suggested that the specific histological findings (in terms of villous atrophy, crypt hyperplasia, and cellular infiltration of the lamina propria) be associated with a T-cell activation mechanism (8,(16)(17)(18)(19)(20). Group II was referred to as 'epithelial dysplasia group' by adding microvillous inclusion disease, microvillous dysplasia, and microvillous atrophy to this group, because this represented histological dysplasia and familial conditions seen in group II in European study (3,15,(21)(22)(23)(24). In a recent study, 29% of children affected by intractable diarrhea with persistent villous atrophy (immune enteropathy group) fulfilled the criteria of autoimmune enteropathy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Microvillous atrophy/inclusion disease can be recognized by performing periodic acid-Schiff stain and electron microscopy (3,10). Four cases of microvillous inclusion disease included in the epithelial dysplasia group have already been published (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Fue descrito por primera vez en 1978 por David Andersen et al quien reportó un grupo de 5 lactantes con diarrea persistente severa de inicio neonatal y hallazgos característicos comunes en la histología intestinal 1,2 . Actualmente se estima su prevalencia en < 1:1.000.000 y hay pocos casos conocidos en el mundo 3 .…”
Section: Introductionunclassified